Aspectos autoecológicos e silviculturais de Eugenia involucrata DC. - Prado, Analissa Pase do (2009)
This study aimed to obtain scientific information about the species Eugenia involucrata DC (wild cherry), through analysis of ecological and silvicultural parameters. Initially, in a remnant of Decidual Seasonal Forest, at the Army Instruction Center of Santa Maria (53 ° 52'O and 29 ° 46'S), the trees with ≥ 30 cm were measured in 14 plots of 20 x 100 m, in four parallel tracks. These plots were subdivided to observe too the population with <30 cm and seed rain. In the strips with 20 m wide and varied length (total of 8.8 ha), 23 matrix trees ≥ 30 cm were selected in which the reproductive phenology was monitored between August and December 2007. In November, the seeds were collected and beneficiated, and one sample was used in seed analysis, for germination test in substrates (paper roll and vermiculite), moisture content, thousand kernel weight, tetrazolium test and electric conductivity. The other sample of the seeds was used to assess the development of the seedlings which were produced in containers of four sizes (tubes 53, 115, 180 and 280 cm3), in the nursery and field. In the remnant, the species was presented with a stable population, with entrance fee and no mortality was found, despite the reproductive season. In the population ≥ 30 cm, it was observed an average increase of 0.5 cm yr-1 and cluster distribution. In this class, the species showed six individuals per hectare, with 53 individuals with potential for selection in 8.8 ha. The flowering stage was in the months of September to October, and the fruiting process from October to November. According to the effective number (Ne), in order to represent the population, at least 60 fruits from the 23 trees should participate in the collection; however, only ten individuals produced fruit with varied intensity, forming the plot used in the study. In the laboratory, no significant difference between substrates (41.9% of germination) was found, in the tetrazolium test, in the 24 hours of preparation, cross-sectional and 3 hours in a solution 0.05%, the tissues were visible; the electric conductivity found was 3.54 for 25 mL, 1.93 for 50 mL and 1.48 for 75 mL. There were no significant differences in the emergence and seedling size for the containers of different sizes, reaching average height (h), stem diameter (dc) and ratio of height to diameter ratio (h/d): 6.91 cm, 2.27 mm and 3.06, respectively, after 330 days in the nursery. In the field, the indifference in size remained, resulting after 330 days, h, dc and h/d, equal to 23.86 cm, 4.26 mm and 5.68, respectively. The remnant has the potential for collection, however, it will depend on the selection of a large number of trees (considering the individual s variability production); in the germination tests, the paper roll allows a greater precision in the analysis, with the first count at 25 days; for the production of seedlings, the 53 cm³ container can be used.